E-Learning and Digital Education in the Twenty-First Century 2022
DOI: 10.5772/intechopen.95071
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Remote Teaching during COVID-19 Pandemic: Roles of Educators in Malaysia

Abstract: This chapter responds to the needs of educators in preparing to teach online fully due to the pandemic, COVID-19. This scenario becomes the new normal in the teaching and learning process during the COVID-19 pandemic. The main objective of this chapter is to investigate the roles of educators in one public higher learning institution in Malaysia during emergency remote teaching due to the COVID-19 outbreak. Emergency remote teaching is argued to be the answer to the sudden change from face-to-face teaching to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…They used both simple and complex tools and applications; they used the school page on Facebook, the messenger, WhatsApp, Google applications, Zoom applications, Screencast-O-matics, and recently used the Microsoft Teams program. That corresponds with the findings of [4], [16], [18] studies. Interactive teaching strategies was one of the best practices that help to stimulate students' learning and motivate them in many ways; some students prefer to participate in extracurricular activities that reveal their interests and talents in different ways; some students who have moderate abilities in frontal teaching became active and more engaged in online learning [28], [29].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…They used both simple and complex tools and applications; they used the school page on Facebook, the messenger, WhatsApp, Google applications, Zoom applications, Screencast-O-matics, and recently used the Microsoft Teams program. That corresponds with the findings of [4], [16], [18] studies. Interactive teaching strategies was one of the best practices that help to stimulate students' learning and motivate them in many ways; some students prefer to participate in extracurricular activities that reveal their interests and talents in different ways; some students who have moderate abilities in frontal teaching became active and more engaged in online learning [28], [29].…”
Section: Discussionsupporting
confidence: 93%
“…In Palestine, some educational institutions have adopted different approaches since the pandemic at the beginning of March 2020 [14], [17], online learning was adopted in schools and higher education institutions depending on the institution's capabilities and willingness to offer a good choice, the extent of the local community's acceptance of the new educational practices, and the extent of students' interaction and acceptance. Therefore, most teachers looked for free platforms and social media channels to support students' learning [18]. Some teachers could sharpen their skills to sustain the online teaching and learning processes [19] using these free resources and implemented effective strategies [20].…”
Section: Contributionmentioning
confidence: 99%
“…This claim is substantiated by a study conducted by Aguilera-Hermida (2020), which found that one of the reasons students were not in favour of ODL is because the lack of skills hampered them in using the online application to complete assignments and that they had to spend more time learning to use the new applications. Because of that, they had to spend more money to subscribe to better and reliable internet service, which provides faster internet connectivity (Juhary, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In UiTM, three leading platforms, namely Google classroom, Microsoft teams, UFuture (institution LMS), and other platforms such as WhatsApp and Telegram, were mainly used to teach and learn English. Despite the teachers' availability and use of different platforms to teach, there were persistent concerns about the ability of the students to learn via ODL, especially those from parts of the country where Internet connectivity was limited (Juhary, 2020;Selvanathan et al 2020).…”
Section: Open and Distance Learning (Odl) Experience In Uitmmentioning
confidence: 99%
“…Face-to-face T&L in all educational institutions was disrupted as a result of the spread of Covid-19. The Malaysian Ministry of Education (MOE) has directed T&L sessions to be held online to prevent the spread of viruses among students and to ensure that no student falls behind in their studies (Juhary, 2020).…”
Section: Introductionmentioning
confidence: 99%